Pediatric robotic‐assisted laparoscopic ureterocalycostomy: Salient tips and technical modifications for optimal repair. Issue 1 (14th November 2020) - Adamic, B. L.; Lombardo, A.; Andolfi, C.; Hatcher, D.; Gundeti, M. S.
Abstract: Introduction: Ureterocalycostomy is a necessary option for renal salvage in cases where conventional reconstructions have failed or as a primary option in anatomic situations such as intrarenal pelvis, malrotated, or horseshoe kidney. The primary principle of this procedure is to allow for dependent drainage. Ureterocalycostomy is often difficult due to extensive scar tissue and may be complicated by bleeding in the setting of a normal functioning lower pole cortex, compared to thin renal cortex and poor renal function as seen in end‐spectrum of the obstruction. Identification of a dependent calyx and hemostasis can be difficult when there is a normal cortical thickness. Though the vascular control of hilum is an option, we suggest some simple tips to avoid this step and optimize surgical results. We present our experience and salient technical tips with pediatric robotic‐assisted laparoscopic ureterocalycostomy and provide a step‐by‐step video. Methods: Four patients underwent robotic‐assisted laparoscopic ureterocalycostomy between the years 2012 and 2016 by a single surgeon. Perioperative outcomes measured included operative time, hospital stay, pain relief, degree of hydronephrosis on postoperative ultrasound at 3 months, and renal scintigraphy as needed. We describe the operative procedure and provide tips on identifying a dependent lower pole calyx with flexible nephroscopy and needle puncture, the use of harmonic scalpel for incision of the lower pole cortex, and anastomosis by pre‐placement of interrupted sutures as the urothelium of the renal calyces is thin and friable. Results: Patients ranged in age between 11 months and 14 years old. Three of four patients had one prior pyeloplasty, and one patient had two prior pyeloplasties. Mean operative time (incision to closure) was 208 minutes. No Clavien‐Dindo 30‐day complications were encountered and no patients required blood transfusion. Anatomic success was reported in all patients with a mean follow‐up of 4.46 years; however, one patient ultimately required nephrectomy despite patent anastomosis, which would not drain due to a capacious pelvis. Conclusions: Robotic‐assisted laparoscopic ureterocalycostomy is feasible in re‐operative cases with extensive scaring and in patients with normal lower pole renal cortex. We offer tips to allow for safe and proficient performance of this procedure.